Effect of Alkali Treatment of Wheat Straw on Adsorption of Cu(II) under Acidic Condition. (3rd July 2016) - Guo, Yiping; Zhu, Weiyong; Li, Guoting; Wang, Xiaomin; Zhu, Lingfeng
Abstract : The convenient and feasible pretreatment method of alkali treatment is very common in the degradation process of wheat straw. However, its utilization in the pretreatment of wheat straw as alternative adsorbents for aqueous heavy metals remediation is rarely reported. The present study investigated the removal efficiency of Cu(II) ions using wheat straw with alkali pretreatment. The condition of alkali treatment on wheat straw was optimized with the adsorption capacity of Cu(II) as indicator using single-factor experiments. The influences of wheat straw dosages, pH values, contact time, and temperatures on adsorption performance for both untreated wheat straw (UWS) and alkali-treated wheat straw (AWS) were investigated. Results showed that the relatively large removal rate of Cu(II) could be obtained, and chemical behavior occurred during the adsorption process. Characteristic analysis found that the major function of alkali treatment to wheat straw was to introduce the hydroxy group, which resulted in the increase of -C-O- group. Although the adsorption capacity is not as high as the one of ligands supported adsorbents, the method is easy to operate and has a wide range of application; at the same time, it could realize both purposes of treating heavy metal pollution and solid wastes.